Edukasi Nutrisi Ibu Hamil Selama Pandemi COVID-19 di Desa Melinggih Kelod, Kecamatan Payangan, Kabupaten Gianyar - Rima Kusuma Ningrum; Dewa Ayu Agung Alit Suka Astini; A. A. S. Ayu Santhi Sueningrum (Warmadewa Minesterium Medical Journal, 2022)
During the pandemic, pregnant women are a group at risk for nutritional deficiencies. This can happen to all pregnant women, including in Melinggih Kelod Village, Payangan District, Gianyar Regency, Bali which is the village chosen for the implementation of the COME 1000 HAK Program at FHMS Unwar. Therefore, the service community team held a nutrition education program for pregnant women in Melinggih Kelod Village. The Service Team carries out this activity by coordinating with the village. This activity also involves village cadres as an effort to sustain the program. The role of village cadres is very important as a leading mover in changing knowledge, attitudes, behavior related to nutrition needed by pregnant women. The nutrition education counseling activity for pregnant women during the COVID-19 pandemic was attended by 10 pregnant women participants and 3 village cadres in Melinggih Kelod Village. Program evaluation is done by pretest and posttest. The percentage of pregnant women's understanding of nutrition education counseling increased by 20 point as seen from the results of the pretest and posttest. This increase is expected to facilitate the process of pregnancy to delivery and the child conceived is healthy according to gestational age. This is expected to prevent the risk of stunting in infants and children.